Normofractionated and moderately hypofractionated proton therapy: comparison of acute toxicity and early quality of life outcomes - Pelak, Maciej J.; Flechl, Birgit; Hug, Eugen; Galalae, Razvan; Konrath, Lisa; Góra, Joanna; Fossati, Piero; Lütgendorf-Caucig, Carola; Tubin, Slavisa; Konstantinovic, Rastko; Mock, Ulrike; Fussl, Christoph; et al. (Frontiers in Oncology, 2022)
Aim Data on the safety of moderately hypofractionated proton beam therapy (PBT) are limited. The aim of this study is to compare the acute toxicity and early quality of life (QoL) outcomes of normofractionated (nPBT) and hypofractionated PBT (hPBT). Material and methods We prospectively compared acute toxicity and QoL between patients treated with nPBT (dose per fraction 1.8–2.3 Gy, n = 90) and hPBT (dose per fraction 2.5–3.1 Gy, n = 49) in following locations: head and neck (H&N, n = 85), abdomen and pelvis (A&P, n = 43), and other soft tissue (ST, n = 11). The toxicities were grouped into categories—mucosal, skin, and other sites—and evaluated according to the Common Terminology Criteria for Adverse Events (CTCAE) version 4.03 at baseline, treatment completion, and 3 months after PBT completion. QoL was evaluated with the European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire (QLQ)-C30 scale for all locations and additionally with EORTC QLQ-HN35 for H&N patients. Results Overall, the highest toxicity grades of G0, G1, G2, and G3 were observed in 7 (5%), 40 (28.8%), 78 (56.1%), and 15 (10.8%) patients, respectively. According to organ and site, no statistically significant differences were detected in the majority of toxicity comparisons (66.7%). For A&P, hPBT showed a more favorable toxicity profile as compared to nPBT with a higher frequency of G0 and G1 and a lower frequency of G2 and G3 events (p = 0.04), more patients with improvement (95.7% vs 70%, p = 0.023), and full resolution of toxicities (87% vs 50%, p = 0.008). Skin toxicity was unanimously milder for hPBT compared to nPBT in A&P and ST locations (p = 0.018 and p = 0.025, respectively). No significant differences in QoL were observed in 97% of comparisons for QLQ-C30 scale except for loss of appetite in H&N patients (+33.3 for nPBT and 0 for hPBT, p = 0.02) and role functioning for A&P patients (0 for nPBT vs +16.7 hPBT, p = 0.003). For QLQ-HN35, 97.9% of comparisons did not reveal significant differences, with pain as the only scale varying between the groups (−8.33 vs −25, p = 0.016). Conclusion Hypofractionated proton therapy offers non-inferior early safety and QoL as compared to normofractionated irradiation and warrants further clinical investigation.